THE USABILITY OF I-SUYYAH: A MOBILE TOURISM APPLICATION FOR ARAB TOURISTS IN MALAYSIA - Wan Daud, Wan Ab Aziz; Abdul Ghani, Mohammad Taufiq; Amiruddin, Ahmad Zaki; Abdul Ghani, Kamarulzaman; Abdul Rahman, Ahmad (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Globalisation and the rapid growth of technologies call for ease and automation in different aspects, including in tourism. Tourism is an important sector in Malaysia as it generates income for the country. In recent years, Malaysia has seen a surge in the arrival of high-spending Arab tourists. This reflects the need to provide a tool, specifically a tourism mobile application in the Arabic language, that could help ease their journey in Malaysia. Thus, this study aims to determine the usability of the i-Suyyah mobile application for Arab tourists in Malaysia. The data obtained were analysed using the Fuzzy Delphi method, and twelve experts were selected to analyse the fuzziness consensus. It was found that the i-Suyyah mobile application recorded a high percentage of expert consensus, specifically on its usability. All usability items have reached unity with the threshold value of d 0.2, and the percentage of consensus among the expert group is more than 83%.